2016
DOI: 10.1038/ncomms11640
|View full text |Cite
|
Sign up to set email alerts
|

MTHFD1 controls DNA methylation in Arabidopsis

Abstract: DNA methylation is an epigenetic mechanism that has important functions in transcriptional silencing and is associated with repressive histone methylation (H3K9me). To further investigate silencing mechanisms, we screened a mutagenized Arabidopsis thaliana population for expression of SDCpro-GFP, redundantly controlled by DNA methyltransferases DRM2 and CMT3. Here, we identify the hypomorphic mutant mthfd1-1, carrying a mutation (R175Q) in the cytoplasmic bifunctional methylenetetrahydrofolate dehydrogenase/me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 70 publications
3
48
0
Order By: Relevance
“…Third, the increased SAH in mat4 would compete with SAM and decrease SAM accessibility to methyltransferases, which mostly reduced the CHG and CHH methylation and H3K9me. Similar results have been observed in both fpgs1 and mthfd1 mutants (Zhou et al, 2013;Groth et al, 2016). Both fpgs1 and mthfd1 mutants accumulate relatively more SAH, which leads to a decreased ratio of SAM/SAH (Zhou et al, 2013;Groth et al, 2016).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Third, the increased SAH in mat4 would compete with SAM and decrease SAM accessibility to methyltransferases, which mostly reduced the CHG and CHH methylation and H3K9me. Similar results have been observed in both fpgs1 and mthfd1 mutants (Zhou et al, 2013;Groth et al, 2016). Both fpgs1 and mthfd1 mutants accumulate relatively more SAH, which leads to a decreased ratio of SAM/SAH (Zhou et al, 2013;Groth et al, 2016).…”
Section: Discussionsupporting
confidence: 80%
“…Treatment with sulfamethazine, which is a structural analog and competitor of p-aminobenzoic acid, the precursor of folate, causes the release of endogenous transposons and repeat elements and the reduction of DNA methylation levels and H3K9me2 (Zhang et al, 2012). A mutation in the cytoplasmic bifunctional methylenetetrahydrofolate dehydrogenase/methenyltetrahydrofolate cyclohydrolase (MTHFD1) leads to decreased levels of oxidized tetrahydrofolates, DNA hypomethylation, loss of H3K9me, and transposon reactivation (Groth et al, 2016).…”
mentioning
confidence: 99%
“…However, (i) and (ii) are confounded by the role of CMT3 in maintaining mCHG at transposons and other regions of the genome [25]. (iii) The addition of a methyl group to a cytosine requires the transcription and translation of methyltransferases and protein complexes, and is a biochemical reaction with energetic and metabolic costs [35]. With costs, benefits most likely ensue.…”
Section: Gbm Function Remains Enigmaticmentioning
confidence: 99%
“…Intriguingly, this aspect of FOCM could have wider implications, as recently it has been shown that changes to MTHFD1 can affect the regulation of DNA methylation. Groth et al (2016) [102] identified a mutant (mthfd1-1) in Arabidopsis thaliana, which carried a mutation in cytoplasmic MTHFD1. This mutant suffered from accumulation of Hcy and SAM, coupled with extensive genome-wide hypomethylation.…”
Section: Rationale For Computationally Integrating Focm and The Dna Mmentioning
confidence: 99%